Smartphone-Based Natural Environment Electroencephalogram Experimentation-Opportunities and Challenges - Hazarika, Doli; Chanda, Souptick; Gupta, Cota Navin (2022 IEEE-EMBS Conference on Biomedical Engineering and Sciences (IECBES), 2022)
Using a smartphone for Electroencephalogram (EEG) based research in the natural environment is a growing field of study. It brings attention to device portability, participant mobility, and system specifications. This article discusses the most recent developments in the field of EEG investigations using smartphones in natural environments, for healthy and clinical applications. We integrate the current trends in smartphone-based EEG studies, namely experimental paradigms, electrode/hardware compatibility, preprocessing frameworks, classifiers, and software apps. However, smartphone devices have inherent limitations like computational time and algorithm performance. Implementing artifact reduction and classification algorithms together in an android smartphone app is still speculative, and possible solutions are proposed. This review presents a holistic insight into our current understanding and challenges of the smartphone's role in natural environment electroencephalogram trials. Clinical Relevance-These portable smartphone-based EEG systems will be useful in monitoring individuals with psychiatric diseases, in addition to human brain applications in a natural setting. With ubiquitous availability of internet on smartphones, telemedicine is another possible application.